(untitled) (Fiep Bulletin - online, 2011)
The objective of this study is to chech Vo2 maximum values measured by a 12 minutes Cooper´s test in physical education teachers, attending Lato Sensu Specialization in the Instituto Batista de Ensino Superior de Alagoas – module of physical and sporting conditioning. The experimental sample was composed by volunteers, all of them physical education teachers, divided in 8 male and 2 female. It was evaluated Vo2 maximum of participants through the obtained results in Cooper´s test of 12 minutes, placed in treadmills, in the fitting area of Gymnasium FormaFIT, Maceió-Al. In the found results the most of the volunteers presented maximum consume of oxygen ( Vo2 max ) under 30 ml ( kg.min )¹ , meaning that the majority presents aerobic conditioning level classified in awful, bad and regular, in accord to the Cooper´s protocol so that they need to improve their cardiorespiratory capacity.